Evaluating Payback Time for Implementing Manufacturing Execution System (MES) - Hautala, Joni (My University, 2015)
Tougher competition and complex supply chain requires nowadays better and better manufacturing execution system to improve delivery punctuality, efficiency and business performance. The Manufacturing Execution System enables production data collection, production planning, and production monitoring and material traceability and also supports the quality management and production data reporting. The Purpose of this study is to investigate a case company and present the potential financial benefits of the Manufacturing Execution System (MES) implementation. The study presents the calculated length of the payback period by using financial benefits. In addition, the investment soundness and profitability is estimated from the target company point of view, using a number of the investment decision-making methods. The thesis is divided into theoretical part and empirical part. The theoretical chapters based on the literature: from the perspective of manufacturing execution system and investment decision methods. The empirical part is divided into two research questions: How to evaluate payback time for MES and what benefits does it produce as a system for companies? What could be the benefits and the payback time for implementing MES for the case company? As a result, a good understanding of the Manufacturing Execution System (MES) was gained, and find out that benefits by using system in case company. The Manufacturing Execution System was found to fit the case company`s activities, because the characteristic of the system supports and improves efficiency in current operating systems. Based on the perceived benefits in the case company the payback time for the MES is 27 months. The financial savings in the case company is achieved with a transparent and flow in production control, and the optimization of intermediate storages. The payback period was found as very appealing investment and reasonable to implement.
Keywords: Manufacturing Execution System; MES; Payback time; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|